Effective School Performance Stages at Public Senior High Schools in Indonesia - Indra, Ristapawa; Kustati, Martin (AT-TALIM, 2016)
The purpose of this study is to evaluate the stages of effective school performance based on 11 characteristics of effective schools as well as to evaluate the level of correlation between individual characteristics of effective schools and the contribution of the school principal leadership to an effective school. 60 school principals and 105 teachers in 16 schools became sample of the research. The number of teachers took as many as 7 to 10 people for each school. The quantitative data were obtained through a set of instruments on 11 characteristics of effective schools. The data were then analyzed descriptively using frequency, min score, percentage, standard deviation, and inferential statistics (Pearsonâs correlation, simple linear regression). Findings showed the stages of effective school performance of Public Senior High Schools in Padang as perceived by the principals and teachers were very high. There was a significant correlation between the professional principal leadership with the realization of 11 characteristics of effective schools. The professional principal leadership contributed as much as 58.5% to the realization of 11 characteristics of effective schools in Public Senior High Schools in Padang while the other percentage was contributed by other variabels not included in this study. The principal leadership was an important factor for the realization of 11 characteristics of effective schools in Public Senior High Schools in Padang.